Formulation and Evaluation of Herbal Gel Containing Fumariaindica Extract and Isolated Compounds for Anti-Psoriatic Activity - Srivastava, Shilpa; Gupta, Naveen; Patel, Ganesh Prasad; Singh, Pinky; Gupta, Puneet (International Journal of Aquatic Research and Environmental Studies, 2026)
Psoriasis is a chronic inflammatory skin disorder associated with oxidative stress, keratinocyte hyperproliferation, and immune dysregulation. The present study aimed to formulate and evaluate herbal gel formulations containing ethanolic extract and isolated compounds from Fumariaindica for anti-psoriatic activity. The aerial parts of Fumariaindica were collected, authenticated, and subjected to physicochemical, phytochemical, and chromatographic analysis. Two bioactive alkaloids, protopine (FI-1) and corydomine (FI-2), were isolated and characterized by spectral methods. Herbal gels (FG1–FG5) containing crude extract and isolated compounds were prepared and evaluated for physicochemical parameters, antioxidant activity, cytokine modulation, PASI score, Baker’s score, and histopathological changes in imiquimod-induced psoriatic mice. Among all formulations, FG5 containing 2% FI-2 demonstrated superior spreadability, viscosity, antioxidant activity, cytokine suppression, and anti-psoriatic efficacy. The formulation significantly reduced erythema, scaling, epidermal hyperplasia, and pro-inflammatory cytokines (TNF-α, IL-6, IL-17). The study suggests that Fumariaindica isolated compounds possess promising anti-psoriatic potential and may serve as effective topical therapeutic agents.